Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1533033819859447
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1254 Functions as a Tumor Suppressor in Oral Squamous Cell Carcinoma by Targeting CD36

Abstract: Oral squamous cell carcinoma is one of the most common cancers around the world. The patients with oral squamous cell carcinoma are often diagnosed at late stages, leading to unfavorable prognosis. MicroRNAs might function as oncogenes or tumor suppressor genes in the tumorigenesis of cancer. This study aimed to explore the role of miR-1254 in oral squamous cell carcinoma. We examined the expression levels of miR-1254 in oral squamous cell carcinoma tissue samples and cell line.Proliferation and invasion assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…22 Chen and colleagues have reported that miR-1254 may restrain the progression of OSCC by downregulating CD36, which may also represent an effective treatment strategy for affected patients. 23 In the present study, we have documented that miR-105 is upregulated in human OSCC tissues and cell lines when compared with non-cancerous tissues and HOK cells, respectively. We have demonstrated that miR-105 expression is closely associated with tumor size as well as clinical and differentiation stages.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…22 Chen and colleagues have reported that miR-1254 may restrain the progression of OSCC by downregulating CD36, which may also represent an effective treatment strategy for affected patients. 23 In the present study, we have documented that miR-105 is upregulated in human OSCC tissues and cell lines when compared with non-cancerous tissues and HOK cells, respectively. We have demonstrated that miR-105 expression is closely associated with tumor size as well as clinical and differentiation stages.…”
Section: Discussionsupporting
confidence: 50%
“… 22 Chen and colleagues have reported that miR-1254 may restrain the progression of OSCC by downregulating CD36, which may also represent an effective treatment strategy for affected patients. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that aberrant expression of miRNAs promoted proliferation, migration, invasion and metastasis of HCC cells 30 . It was reported that miR-1254 had anti-tumor activity in oral squamous cell carcinoma by targeting CD36 31 . Another study found that miR-1254 targeted secreted frizzled related protein 1 (SFRP1), a Wnt/β-catenin pathway antagonist, to promote lung cancer cell proliferation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Targets and functional roles of miRNAs in oral cancer. OSCC (61). Similarly, miR-377 and miR-23a-3p suppressed cell proliferation and promoted apoptosis in OSCC, suggesting that both miR-377 and miR-23a-3p may prove to be of value as therapeutic targets for OSCC in the future (63,64).…”
Section: Mirnas and Oral Cancer Occurrence And Progressionmentioning
confidence: 95%